Fábrica do corpo neoliberal: ditos e não ditos dos discursos midiáticos sobre beleza e saúde - Lovato, Sabina Ribeiro (2019)
This research selects as its theme the production of media discourses about beauty and health and its subjectifying ways in the context of our contemporary consumption society, guided by communications and consumption theories, with emphasis on reflections about neoliberalism and biosociality. Our research problem is defined by the following question: How does discursive interactions are constituted in between media discourses about beauty and health, considering the articulations between communication and consumption in the making of the neoliberal subject and in the promotion of biosocialities? To answer that, we develop a discourse analysis having as its empiric object the institutional campaign ―Safe Silicone‖, by Johnson & Johnson, mapping the media convocations which promotes a contemporary subjectivity that constitutes the feminine neoliberal subject. Throughout this work, we also analyse scattered media texts about breast implants and plastic surgery, contextualizing its discursive formation. The theoretical reference is composed by three axes: Communications and Consumption, with Silverstone, Douglas and Isherwood, Hoff and Sodré; Neoliberalism and Post-Feminism, with Dardot and Laval, Boltanski and Chiapello and Elias, Gill and Scharff; and Biopolitcs and Biosociality, with Foucault, Rabinow, Ortega, Hoff and Jarrín. As theoretical-methodological conduct we have the French Discourse Analysis and its notions of saying and sayings and discursive formation. Thus, inspired by the studies by Elias, Gill and Scharff on post-feminism, considered by those authors as gendered neoliberalism, we identify and analyse the convocations aimed at the feminine neoliberal subject found in the ―Safe Silicone‖ campaign. As for the results, we notice that, when positive and optimistic affects are mobilized to inculcate the neoliberal ideology of entrepeneurship, the saying and non sayings of the discourse reveal an infantilized subject who engages in aesthetic labour resignified as feminine empowerment. The media discourses silence the risks of breast implants, providing incomplete information to the patient-consumers who seek the self-production of the body by means of plastic surgery.